Impact of an electronic alert notification system embedded in radiologists' workflow on closed-loop communication of critical results: a time series analysis. Issue 7 (15th September 2015) - Lacson, Ronilda; O'Connor, Stacy D; Sahni, V Anik; Roy, Christopher; Dalal, Anuj; Desai, Sonali; Khorasani, Ramin
Abstract : Introduction: Optimal critical test result communication is a Joint Commission national patient safety goal and requires documentation of closed-loop communication among care providers in the medical record. Electronic alert notification systems can facilitate an auditable process for creating alerts for transmission and acknowledgement of critical test results. We evaluated the impact of a patient safety initiative with an alert notification system on reducing critical results lacking documented communication, and assessed potential overuse of the alerting system for communicating results. Methods: We implemented an alert notification system—Alert Notification of Critical Results (ANCR)—in January 2010. We reviewed radiology reports finalised in 2009–2014 which lacked documented communication between the radiologist and another care provider, and assessed the impact of ANCR on the proportion of such reports with critical findings, using trend analysis over 10 semiannual time periods. To evaluate potential overuse of ANCR, we assessed the proportion of reports with non-critical results among provider-communicated reports. Results: The proportion of reports with critical results among reports without documented communication decreased significantly over 4 years (2009–2014) from 0.19 to 0.05 (p<0.0001, Cochran–Armitage trend test). The proportion of provider-communicated reports with non-critical results remained unchanged over time before and after ANCR implementation (0.20 to 0.15, p=0.45, Cochran–Armitage trend test). Conclusions: A patient safety initiative with an alert notification system reduced the proportion of critical results among reports lacking documented communication between care providers. We observed no change in documented communication of non-critical results, suggesting the system did not promote overuse. Future studies are needed to evaluate whether such systems prevent subsequent patient harm.